(untitled) (Revista Educação, Artes e Inclusão, 2024)
This article is a bibliographical and documentary research in a qualitative approach about the main normative landmarks that have been defining the special education policies for children from 0 to 5 years old in brazilian early childhood education. We aim to analyze Special Education in Brazil for children in kindergarten and what public policies point to in order to implement an inclusive, anti-capacitist and democratic early childhood education for all babies, very young children and young children with disabilities, autism spectrum disorders and high abilities/giftedness. The results of this study show that the special education audience in the early childhood education age group needs greater visibility through brazilian educational public policies, especially in pedagogical and curricular actions that guide towards an inclusive educational system in the public and private spheres, giving more emphasis to the needs and knowledge that these subjects bring to the space of the kindergarten, so that the child, in his uniqueness, is the center of the pedagogical planning. Thus, we conclude that inclusive early childhood education is a non-negotiable and irreducible right, since children at this stage of life are subjects in an intense process of formation and human development.